Majorants of functions with vanishing integrals over balls - Ochakovskaya, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We prove the existence of nontrivial functions in Rn , n > 2, with vanishing integrals over balls of fixed radius and given majoranta of growth.